Uji Ekstrak Daun Kumis Kucing Dalam Menurunkan Kadar Alanin Transaminase pada Mencit yang Diinduksi Minyak Goreng Pemanasan Berulang - Meidiana, Steffi; Prasetyo, Diding Heri; sarsono, . (Nexus Biomedika, 2014)
Backgrounds: Orthosiphon stamineus Benth leaves contain various antioxidants like flavonoids, organic acids, and terpenoids. The main active chemical substances which are derived from flavonoids, namely sinensetin, and non-flavonoids, namely rosmarinic acids, have antioxidants activities as free radical scavengers. This study aimed to determine the effects of Orthosiphon stamineus Benth leaves extract in decreasing the levels of ALT in male strain Swiss webster mice induced by reheated cooking oil. Methods: This study was an experimental laboratory with a post test only controlled group design. The samples were 25 male strain Swiss webster mice, 2-3 months old and + 25-30 grams weight, each. Samples were taken incidentally sampling, arranged into 5 groups randomly, consisted of 5 mice each group. The control group (K) was administered distilled water and treatment group 1 (P 1) were administered reheated cooking oil. While treatment group 2 (P 2), treatment group 3 (P 3) and treatment group 4 (P 4) were consecutively administered 3.5 mg, 7.0 mg and 14.0 mg/25 gr BW of Orthosiphon stamineus Benth leaves extract and reheated cooking oil for 14 days. On the 15th day, blood samples were drawn from the mice through plexus retroorbitalis using microtubuler tube then their ALT levels were measured. Data were analyzed using One-way ANOVA (Î± = 0.05) and followed by Post Hoc Multiple Comparisons test (LSD) (Î± = 0.05). Results: Mean rate of alanin transaminase level in group K, P 1, P 2, P 3 andÂ P 4 wereÂ 54.600 + 7.765 U/L;Â â 95.000 + 23.537 U/L; 62.200 + 7.463 U/L; 60.400 + 6.427 U/L and 57.400 + 10.922 U/L, in a row. Conclusions: Orthosiphon stamineus Benth leaves extract decreased alanin transaminase level in mice induced reheated cooking oil. Keywords: ALT, Orthosiphon stamineus Benth leaves extract, reheated cooking oil. Â